PERAN POLA ASUH ORANG TUA DALAM MEMBENTUK KARAKTER ANAK USIA DINI PADA ERA DIGITAL - Mariana Panji Ramadan; Azimatur Rahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of digital technology has significantly transformed the lives of early childhood, where the use of gadgets, the internet, and social media has become an integral part of daily activities, influencing how children learn, interact, and develop their character. This condition highlights the crucial role of parents in applying parenting practices that are not only adaptive to technological advancements but also capable of instilling moral, social, and emotional values in a balanced manner. Without proper guidance, technology use may lead to various developmental issues, such as decreased empathy, increased individualistic tendencies, and consumptive behavior among children. This study aims to describe parental parenting practices in assisting early childhood in the digital era, analyze their contribution to children's character development, and identify the challenges and strategies employed by parents in responding to these dynamics. This research employs a qualitative approach with a case study method, involving parents with children aged 4-6 years as research subjects. Data were collected through in-depth interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The expected outcomes of this study include publication in a nationally accredited journal, the development of a conceptual model of effective parenting in the digital era, and practical recommendations for parents and early childhood educators in fostering children's character through a balanced approach between fundamental values and the demands of technological development.